Desulfurization of Model Oil through Adsorption over Activated Charcoal and Bentonite Clay Composites - Ullah, Sana; Hussain, Sajjad; Ahmad, Waqas; Khan, Hammad; Khan, Khurram Imran; Khan, Saad Ullah; Khan, Sabir [UNESP] (Wiley, 2020)
Adsorption of dibenzothiophene (DBT) from model oil was investigated using composites of pure activated charcoal and pure bentonite clay. DBT adsorption was carried out in batch mode experiments at laboratory scale, where the developed composite materials showed a synergistic effect in removal of DBT from the model oil in terms of improved surface acidity of the pure activated charcoal and mesoporous structure of the pure bentonite clay. Thermodynamics, kinetics, and optimization of various adsorption parameters were investigated. Kinetic analyses proved that DBT adsorption followed pseudo-second-order kinetics. To study the thermodynamics of the adsorption, different isotherm adsorption models were applied. The Langmuir isotherm best fitted to the adsorption data. Various thermodynamic parameters were evaluated, including Gibbs free energy, entropy, and enthalpy.
Keywords: Activated charcoal; Adsorption; Bentonite clay; Desulfurization; Dibenzothiophene